2016
DOI: 10.2147/cia.s117292
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity pattern in patients with late monocular blindness in middle-age using amplitude of low-frequency fluctuation: a resting-state functional MRI study

Abstract: ObjectivePrevious reports have demonstrated significant brain activity changes in bilateral blindness, whereas brain activity changes in late monocular blindness (MB) at rest are not well studied. Our study aimed to investigate spontaneous brain activity in patients with late middle-aged MB using the amplitude of low-frequency fluctuation (ALFF) method and their relationship with clinical features.MethodsA total of 32 patients with MB (25 males and 7 females) and 32 healthy control (HC) subjects (25 males and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…Moreover, The V1 is the core part of the visual pathways [ 21 ]. In our previous study, we demonstrated that the MB showed decreased amplitude of low-frequency fluctuation in right cuneus [ 22 ]. Besides, A recent research exhibited that the MB patients showed lower gray matter volume in the bilateral superior lateral occipital cortices compared with health controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, The V1 is the core part of the visual pathways [ 21 ]. In our previous study, we demonstrated that the MB showed decreased amplitude of low-frequency fluctuation in right cuneus [ 22 ]. Besides, A recent research exhibited that the MB patients showed lower gray matter volume in the bilateral superior lateral occipital cortices compared with health controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with blindness have shown enhanced SMG functional connectivity (Heine et al, 2015). Li et al (2016) found that patients with MB have elevated SMG amplitude of low-frequency fluctuation (ALFF) values on the left side, and MB was unable to activate the SMG. Therefore, we speculated that the brain coding function of speech coding and processing is a compensatory mechanism for the loss of visual acuity in patients with MB.…”
Section: Ta B L E 2 Gmv Differences Between Mb and Nc Groupsmentioning
confidence: 99%
“… 11 , 12 In our previous studies, the ALFF method was successfully applied to the investigation of spontaneous brain activities in various diseases such as glaucoma and blindness. 13 , 14 Thus, the ALFF method was proven to be a reliable and effective resting-state fMRI technique.…”
Section: Introductionmentioning
confidence: 99%